C-PTFE / PVDF hollow fiber membrane for oil-water separation and preparation method thereof

By using NIPS method and carbonization process to prepare C-PTFE/PVDF hollow fiber membranes on the basis of PTFE and PVDF powders, the problems of complex preparation and insufficient performance of PTFE membranes in the prior art are solved, and efficient oil-water separation effect is achieved.

CN119838446AInactive Publication Date: 2025-04-18SICHUAN LIGE NEW MATERIALS CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510213117.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-25
Publication Date
2025-04-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the prior art, the preparation process of PTFE film is complex, has low porosity and uneven pore size distribution, making it difficult to prepare efficient oil-water separation membranes through simple and fast methods.

Method used

After drying PTFE and PVDF powder in a drying oven, mix it in DMAc and dissolve it, and then PTFE/PVDF hollow fiber membrane embryos were prepared by NIPS method, and partially carbonized under a nitrogen protective atmosphere to obtain C-PTFE/PVDF hollow fiber membranes.

Benefits of technology

It achieves high porosity, excellent water flux and hydrophobicity, significantly improves the separation efficiency of oil and water mixture, and is suitable for use in water purification and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119838446A_ABST
    Figure CN119838446A_ABST
Patent Text Reader

Abstract

The invention discloses a C-PTFE / PVDF hollow fiber membrane for oil-water separation and a preparation method of the C-PTFE / PVDF hollow fiber membrane. The preparation method comprises the following steps: dispersing PTFE powder in a polyvinylidene fluoride solution to obtain a PTFE suspension, and firstly, preparing a PTFE / PVDF hollow fiber membrane blank by using a dry-wet phase inversion method; and then carrying out partial carbonization in a nitrogen atmosphere to prepare the partially carbonized PTFE / PVDF hollow fiber membrane. A scanning electron microscope and element analysis show that PVDF in the PTFE / PVDF membrane blank is partially carbonized, and residual fluorocarbon organic matters and molten PTFE particles form the hollow fiber membrane with good toughness and hydrophobicity. The C-PTFE / PVDF hollow fiber membrane has higher porosity, water flux and water contact angle, and shows better separation performance on an oil-water mixture.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of functional materials and oil-water separation, and in particular to a C-PTFE / PVDF hollow fiber membrane for oil-water separation and a preparation method thereof. Background Art

[0002] In recent years, membrane separation technology has been recognized as an environmentally friendly green method for oil-water separation due to its simple separation method, easy scale-up, and no secondary pollution. Membrane separation technology has higher separation efficiency than other methods in separating oil-water emulsions, especially stable emulsions. At present, the ultrafiltration membranes used for oil-water separation mainly include PVDF membrane, PTFE membrane, polypropylene (PP) membrane, polyethersulfone (PES) membrane, polysulfone (PS) and ceramic membrane. PTFE is a perfluorocarbon superhydrophobic material with excellent chemical and thermal stability, strong hydrophobicity and high fracture toughness. It is considered to be a good oil-water separation membrane material, which is difficult to form a membrane using a phase inversion method. The PTFE flat or hollow fiber membrane that has been used in commercial applications is mainly prepared by melt extrusion-stretching method, which is prepared by three steps of paste extrusion, stretching and sintering. This method has a complex preparation process, and the prepared membrane has low porosity and uneven pore size distribution. Therefore, it is urgent to study a new method for preparing PTFE membranes that is simple and fast.

[0003] The NIPS (non-solvent induced phase separation) method is to dissolve the polymer membrane material in a solvent to form a membrane solution, and then complete the phase transformation from liquid phase to solid phase in a non-solvent to form a flat or hollow membrane with a dense outside and a sparse inside. The preparation process is simple and it is the main method for preparing flat or hollow fiber membranes. PTFE is insoluble in any solvent and is difficult to form a membrane using the NIPS method. PVDF is a fluorine-containing polymer membrane material composed of fluorocarbon and fluorine hydrogen. It can be dissolved in a variety of organic solvents and has been made into flat and hollow fiber membranes. It is widely used in environmental water treatment fields such as oil-water separation. At present, there are few studies that use or borrow the preparation method of inorganic membranes to blend and modify PVDF and other membrane materials (such as PTFE) to improve their anti-pollution performance. Summary of the invention

[0004] The purpose of the present invention is to provide a C-PTFE / PVDF hollow fiber membrane for oil-water separation and a preparation method thereof in view of the deficiencies of the prior art.

[0005] The present invention provides a method for preparing a C-PTFE / PVDF hollow fiber membrane for oil-water separation, comprising:

[0006] Step 1: Place PTFE and PVDF powders in a drying oven for drying; Add PVDF and PVP into DMAc, stir until completely dissolved, then add PTFE powder, stir to obtain a membrane solution, and then transfer to a hollow fiber membrane spinning machine, let it stand and keep warm, and then use NIPS to prepare a PTFE / PVDF hollow fiber membrane embryo;

[0007] Step 2: Take out the PTFE / PVDF hollow fiber membrane embryo from the deionized water and dry it naturally, then place it in a tubular furnace, use nitrogen as a protective gas, heat it to 380°C, keep it warm for 0.5h, cool it to room temperature and take it out to obtain a C-PTFE / PVDF hollow fiber membrane.

[0008] Furthermore, in step 1, the PTFE and PVDF powders are placed in a drying oven and dried at 80° C. for 24 hours.

[0009] Further, in step 1, PVDF and PVP are added to DMAc and stirred at 50° C. until completely dissolved.

[0010] Furthermore, in step 1, PTFE powder is added and stirred at 50° C. for 18 hours to obtain a membrane liquid.

[0011] Furthermore, in step 1, after standing and keeping warm for 1 hour, a PTFE / PVDF hollow fiber membrane embryo is prepared using NIPS.

[0012] Furthermore, the mass fraction of PTFE in the membrane liquid is 20% to 50%.

[0013] Furthermore, in step 1, the mass fraction of PTFE in the membrane liquid is 25% to 45%.

[0014] Furthermore, in step 2, nitrogen was used as the protective gas, the temperature was raised to 380° C. at 1° C. / min, kept at that temperature for 0.5 h, and then taken out after being cooled to room temperature.

[0015] The present invention also provides a C-PTFE / PVDF hollow fiber membrane for oil-water separation, which is prepared by the preparation method of the C-PTFE / PVDF hollow fiber membrane for oil-water separation as described in the above claims.

[0016] The beneficial effects of the present invention are as follows: A method for preparing a C-PTFE PVDF hollow fiber membrane for oil-water separation of the present invention uses PTFE as a membrane material and PVDF as a binder, and prepares a C-PTFE / PVDF hollow fiber membrane by a NIPS-carbonization method. Scanning electron microscopy and elemental analysis show that the PVDF in the PTFE / PVDF membrane embryo is partially carbonized, and the residual carbon fluorine organic matter and molten PTFE particles form a hollow fiber membrane with good toughness and hydrophobicity. The C-PTFE / PVDF hollow fiber membrane has a higher porosity, water flux and water contact angle, and exhibits better separation performance for oil-water mixtures. The water flux of the C-PTFE / PVDF hollow fiber membrane is as high as 467.67L / (m 2 ·h·MPa), the maximum contact angle is 102°, and the separation efficiency of 1:9 oil-water emulsion mixture can reach 80%. This efficiency can also be improved by optimizing the ratio of PTFE and PVDF, the molding process and the carbonization process, thereby reducing the pore size of the membrane, thereby improving the separation efficiency of the oil-water mixture. This method provides a new idea for the preparation and application of PTFE hollow fibers. The preparation process of the invention is simple to operate, presents good oil-water separation performance and commercial application value, is suitable for promotion and application, has great potential in practical applications, and can be used for water purification, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 TG-DTA graph of the PTFE / PVDF hollow fiber membrane embryo in Example 1 and TG graph of the PTFE / PVDF hollow fiber membrane before and after carbonization;

[0018] Figure 2 FTIR images of PTFE / PVDF hollow fiber membranes before and after carbonization in Example 1;

[0019] Figure 3 XPS images of the PTFE / PVDF hollow fiber membrane before and after carbonization in Example 1 (a) before carbonization, (b) after carbonization;

[0020] Figure 4 Comparison of the microstructures of the hollow fiber membranes before and after carbonization in Examples 1 to 4 (a1) to (d1) before carbonization, (a2) to (d2) after carbonization;

[0021] Figure 5 Examples 1 to 4 are graphs showing changes in water contact angles of the PTFE / PVDF hollow fiber membrane in Example 1 before and after carbonization;

[0022] Figure 6 The graphs of average pore size change and oil droplet size distribution of PTFE / PVDF hollow fiber membranes with different ratios before and after carbonization in Examples 1 to 4 are shown;

[0023] Figure 7 The porosity change diagram of the PTFE / PVDF hollow fiber membranes with different ratios before and after carbonization in Examples 1 to 4;

[0024] Figure 8 The mechanical properties of the PTFE / PVDF hollow fiber membranes with different ratios before and after carbonization in Examples 1 to 4 are shown in (a) before carbonization and (b) after carbonization.

[0025] Fig. 9 The pure water flux diagram (a) of the PTFE / PVDF hollow fiber membranes with different ratios before and after carbonization and the total pure water flux diagram within 3.75 hours (b) in Examples 1 to 4;

[0026] Fig.10 Figure 1 shows the oil-water separation device in Example 1 to Example 4 (a), and the permeation flux and separation efficiency of the PTFE / PVDF hollow fiber membrane (b);

[0027] Fig.11 This is the oil-water separation cycle performance diagram of the M3 hollow fiber membrane in Example 3. DETAILED DESCRIPTION

[0028] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with Examples. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. The specific conditions not indicated in the embodiments are carried out according to conventional conditions or the conditions recommended by the manufacturer, and the reagents or instruments used that do not indicate the manufacturer are all conventional products that can be purchased commercially.

[0029] The technical scheme adopted by the present invention is: PTFE powder is dispersed in polyvinylidene fluoride (PVDF) solution to obtain PTFE suspension, and a PTFE / PVDF hollow fiber membrane embryo is first prepared by dry-wet phase conversion method; then, partial carbonization is performed under nitrogen atmosphere to obtain a partially carbonized PTFE / PVDF hollow fiber membrane. The carbonization process of the PTFE / PVDF hollow fiber membrane embryo, the changes of surface elements and microstructures before and after carbonization of the membrane are studied by thermogravimetric analysis, X-ray photoelectron spectroscopy (XPS) and scanning electron microscopy; finally, the hydrophilic and hydrophobic changes and oil-water separation performance of the membrane are tested. The results show that the PVDF in the PTFE / PVDF hollow fiber membrane embryo undergoes CH rupture at 360-450°C, and the PTFE maintains the original structure, so that a partially carbonized PTFE / PVDF hollow fiber membrane (C-PTFE / PVDF) can be obtained. The pore size of the hollow fiber membrane prepared by the partial carbonization process is reduced, forming a continuous and complete microporous structure. When the PTFE content is 40%, the contact angle of the carbonized membrane reaches 102°, and the hydrophobicity is improved; the permeation flux of 10% simulated oil-containing emulsion wastewater reaches 30L / (m2 h) (transmembrane pressure difference: 0.1MPa), separation efficiency reaches 80%,

[0030] The present invention also relates to a method for preparing the PTFE / PVDF hollow fiber membrane, comprising the following steps:

[0031] 1. Preparation of PTFE / PVDF hollow fiber membrane embryo

[0032] PTFE and PVDF powders were placed in a drying oven and dried at 80°C for 24 hours; PVDF and PVP were added to DMAc according to the mass ratio of PVDF:PVP = 5:1, stirred at 50°C until completely dissolved, and then PTFE powder was added, stirred at 50°C for 18 hours to obtain a membrane solution, which was then transferred to a hollow fiber membrane spinning machine, and after standing and keeping warm for 1 hour, a PTFE / PVDF hollow fiber membrane embryo was prepared using NIPS. The mass fraction of PTFE in the membrane solution was 20% to 50%, and was optimized to be 25% to 45%.

[0033] 2. Preparation of C-PTFE / PVDF hollow fiber membrane

[0034] The PTFE / PVDF hollow fiber membrane embryo was taken out from the deionized water and dried naturally, then placed in a tubular furnace, heated to 380°C at 1°C / min with nitrogen as protective gas, kept warm for 0.5h, cooled to room temperature and taken out to obtain C-PTFE / PVDF.

[0035] The structural characterization and performance testing methods of the prepared C-PTFE / PVDF hollow fiber membrane in this application include:

[0036] 1. Structural Characterization

[0037] 1. The C-PTFE / PVDF membrane sample was broken in liquid nitrogen, fixed on the sample stage, and then vacuum-plated with gold. The microstructure was observed using SEM. The scanning voltage was 20 kV.

[0038] 2. Place the naturally dried PTFE / PVDF membrane embryo sample in a crucible and test the thermogravimetric properties of the membrane using a thermogravimetric analyzer.

[0039] 3. Mix potassium bromide and the membrane sample and press them into tablets. Use infrared spectrometer to test the characteristic elements. The scanning wave number is from 400-1000cm -1

[0040] 4. Use X-ray photoelectron spectrometer to analyze the element changes of the film samples before and after carbonization.

[0041] 5. Use a contact angle meter to measure the water contact angle of the hollow fiber membrane. Take 10 points for each sample and take the average value.

[0042] 6. The pore size of membrane samples was determined using the bubble pressure method using a capillary flow porometry.

[0043] 7. Determine the membrane porosity (δ) by gravimetric method. Cut a certain length of hollow membrane and immerse it in ethanol for 48 hours. Then take it out with tweezers, remove the excess impregnation liquid on the surface, and measure and record the mass m of the wet membrane. 1 and thickness D, and finally put it into an electric drying oven to remove ethanol, and measure and record the mass m of the film 2 , size and thickness D. Measure 3 times and take the average value. Calculate the porosity of the membrane using formula (1):

[0044] δ=(m 2 -m 1 ) / (A·D·ρ) (1)

[0045] Where: A is the area of ​​the sample film, cm 2 ;m 1 and m 2 is the mass of the dry and wet films, g; D is the average thickness of the films, cm; ρ is the density of ethanol (ρ = 0.789 g / mL).

[0046] 8. Use an intelligent tensile testing machine to test the mechanical properties of the hollow fiber membrane. The gauge length of the sample is 60 mm.

[0047] 2. Separation performance test

[0048] 1. Water flux test

[0049] The sealed type I hollow fiber membrane module was placed in a laboratory-made membrane performance flux tester and pre-pressed at 0.1 MPa for 30 min to measure the water flux of the membrane. Five groups were tested continuously, each for 15 min, and the average value was taken. The pure water flux of the membrane was calculated according to formula (2):

[0050] J=V / (A·T) (2)

[0051] Where: J is the pure water flux, L / (m 2 ·h); V is the filtrate volume, L; A is the effective membrane area, m 2 ; T is the time required to obtain the permeate volume, h.

[0052] 2. Oil-water separation test

[0053] Petroleum ether and water were mixed in a volume ratio of 1:9 to prepare a simulated oil-water emulsion mixture as the feed liquid for the oil-water separation test. The hollow fiber membrane was made into an "Ⅰ" component and placed in a homemade membrane performance test system. The oil-water separation was carried out at a pressure of 0.1 MPa, the oil-water separation process was observed, the filtrate volume was recorded, and the feed liquid and filtrate concentrations were determined using a total organic carbon (TOC) instrument. The oil-water separation efficiency was calculated according to the following calculation formula (3):

[0054] R=(1-C 1 / C 2 )×100%(3)

[0055] Where: R is the interception rate, %; C 2 and C 1 Refers to feed solution and permeate concentration, g / L, respectively.

[0056] 3. Oil-water separation cycle performance test

[0057] The C-PTFE / PVDF hollow fiber membrane with the best separation effect was subjected to a cyclic test on oil-water separation performance, with one cycle every 5 hours and a sampling test every 1 hour.

[0058] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with Examples. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. The specific conditions not indicated in the embodiments are carried out according to conventional conditions or the conditions recommended by the manufacturer, and the reagents or instruments used that do not indicate the manufacturer are all conventional products that can be purchased commercially.

[0059] Embodiment 1:

[0060] 1. Preparation of PTFE / PVDF hollow fiber membrane embryo

[0061] PTFE and PVDF powders were placed in a drying oven and dried at 80°C for 24 hours; PVDF and PVP-K30 (polyvinyl pyrrolidone-K30) were added to DMAc (N, N-dimethylacetamide) according to the mass ratio of PVDF:PVP = 5:1, and stirred at 50°C until completely dissolved, and then PTFE powder was added, and stirred at 50°C for 18 hours to obtain a membrane solution, which was then transferred to a hollow fiber membrane spinning machine, and after standing and keeping warm for 1 hour, a PTFE / PVDF hollow fiber membrane embryo was prepared using NIPS. The mass fraction of PTFE in the membrane solution was 30%, and the obtained membrane embryo was marked as M1.

[0062] 2. Preparation of C-PTFE / PVDF hollow fiber membrane

[0063] The PTFE / PVDF hollow fiber membrane embryo was taken out from the deionized water and dried naturally, then placed in a tubular furnace, heated to 380°C at 1°C / min with nitrogen as the protective gas, kept warm for 0.5h, cooled to room temperature and taken out to obtain C-PTFE / PVDF, and the membrane sample was marked M1S.

[0064] Embodiment 2:

[0065] 1. Preparation of PTFE / PVDF hollow fiber membrane embryo

[0066] PTFE and PVDF powders were placed in a drying oven and dried at 80°C for 24 hours; PVDF and PVP-K30 were added to DMAc according to the mass ratio of PVDF:PVP = 5:1, stirred at 50°C until completely dissolved, and then PTFE powder was added, stirred at 50°C for 18 hours to obtain a membrane solution, which was then transferred to a hollow fiber membrane spinning machine, and after standing and keeping warm for 1 hour, a PTFE / PVDF hollow fiber membrane embryo was prepared using NIPS. The mass fraction of PTFE in the membrane solution was 35%, and the obtained membrane embryo was marked as M2.

[0067] 2. Preparation of C-PTFE / PVDF hollow fiber membrane

[0068] The PTFE / PVDF hollow fiber membrane embryo was taken out from the deionized water and dried naturally, then placed in a tubular furnace, heated to 380°C at 1°C / min with nitrogen as the protective gas, kept warm for 0.5h, cooled to room temperature and taken out to obtain C-PTFE / PVDF, and the membrane sample was marked M2S.

[0069] from Fig. 9 It can be seen that rGO@diesel-MS can continuously separate oil and water when used under the external force provided by the pump.

[0070] Embodiment 3:

[0071] 1. Preparation of PTFE / PVDF hollow fiber membrane embryo

[0072] PTFE and PVDF powders were placed in a drying oven and dried at 80°C for 24 hours; PVDF and PVP-K30 were added to DMAc according to the mass ratio of PVDF:PVP = 5:1, stirred at 50°C until completely dissolved, and then PTFE powder was added, stirred at 50°C for 18 hours to obtain a membrane solution, which was then transferred to a hollow fiber membrane spinning machine, and after standing and keeping warm for 1 hour, a PTFE / PVDF hollow fiber membrane embryo was prepared using NIPS. The mass fraction of PTFE in the membrane solution was 40%, and the obtained membrane embryo was marked as M3.

[0073] 2. Preparation of C-PTFE / PVDF hollow fiber membrane

[0074] The PTFE / PVDF hollow fiber membrane embryo was taken out from the deionized water and dried naturally, then placed in a tubular furnace, heated to 380°C at 1°C / min with nitrogen as the protective gas, kept warm for 0.5h, cooled to room temperature and taken out to obtain C-PTFE / PVDF, and the membrane sample was marked M3S.

[0075] Embodiment 4:

[0076] 1. Preparation of PTFE / PVDF hollow fiber membrane embryo

[0077] Place PTFE and PVDF powder in a drying oven at 80°C for 24 hours; add PVDF and PVP-K30 into DMAc according to a certain ratio of PVDF:PVP = 5:1 by mass, stir at 50°C until completely dissolved, then add PTFE powder, stir at 50°C for 18 hours to obtain membrane solution, then transfer to a hollow fiber membrane spinning machine, stand and keep warm for 1 hour, and use NIPS to prepare PTFE / PVDF hollow fiber membrane embryos. The mass fraction of PTFE in the membrane solution is 45%, and the obtained membrane embryo is marked as M4.

[0078] 2. Preparation of C-PTFE / PVDF hollow fiber membrane

[0079] The PTFE / PVDF hollow fiber membrane embryo was taken out from the deionized water and dried naturally, then placed in a tubular furnace, heated to 380°C at 1°C / min with nitrogen as the protective gas, kept warm for 0.5h, cooled to room temperature and taken out to obtain C-PTFE / PVDF, and the membrane sample was marked M4S.

[0080] from Figure 1(a) It can be seen that the thermal weight loss of the PTFE / PVDF membrane embryo in Example 1 is clearly divided into three steps, namely the breakage of CH in PVDF, the breakage of CF and the decomposition of PTFE. The mass loss of the sample at 360-450°C is 6.82%, which is due to the thermal decomposition of the PVDF part in the membrane embryo, corresponding to the α endothermic peak of the DTA curve. The thermal weight loss at 450-500°C is about 9.59%, which is due to the large-scale breakage of the CF bonds in PVDF, and the PVDF in the membrane embryo is basically completely burned out. At 500-600°C, it corresponds to the thermal decomposition of PTFE, corresponding to the endothermic peak of the DTA curve. When the temperature rises to 530°C, the carbon-carbon main chain of PTFE undergoes thermal decomposition, resulting in a sharp drop in quality. When the temperature rises to 650°C, the thermal weight loss reaches a constant mass, corresponding to the complete thermal decomposition of PTFE. According to the thermogravimetric analysis test results of the membrane embryo, 360°C is the lower limit of the carbonization temperature. When the carbonization temperature exceeds 450°C, the mass loss reaches 16.41%, and the CH and CF side chains in PVDF are thermally decomposed, leaving a carbon-carbon skeleton. PTFE will not thermally decompose at 500°C, but will begin to thermally decompose when the temperature exceeds 500°C, which is the carbonization temperature threshold. Therefore, the carbonization temperature range of PTFE / PVDF membrane is 360-450°C, which thermally decomposes the CH side chains of PVDF to form a CC and CF skeleton structure. At this time, the PTFE particles begin to melt and bond together, shrinking the large pores formed by the PTFE particle bridge, and then forming a continuous ultra-microporous structure in the membrane. Figure 1 (b) It can be seen that the PTFE / PVDF hollow fiber membrane before carbonization in Example 1 began to lose mass at 360°C, while the C-PTFE / PVDF membrane after partial carbonization began to lose mass at 450°C. The thermal weight loss was divided into two obvious steps: the decomposition of PVDF and PTFE; 450-500°C was the first step, and the remaining PVDF in the C-PTFE / PVDF membrane was completely burned away; 500-600°C was the decomposition of PTFE, which proved that part of the PVDF in the carbonized C-PTFE / PVDF membrane was decomposed. The mass loss temperature of the partially carbonized C-PTFE / PVDF membrane increased, indicating that the thermal stability of the hollow fiber membrane after carbonization increased.

[0081] from Figure 2 It can be seen that: in Example 1, the PTFE / PVDF membrane embryo before and after carbonization is 1150cm -1 and 1210cm -1 There are two absorption peaks at 1405cm, which are the characteristic peaks of stretching vibration of FCF in PTFE and deformation vibration of FCF. There is no significant change in the characteristic peaks of PTFE before and after carbonization, indicating that PTFE has good thermal stability. -1 The absorption peak at corresponds to the CH 2Deformation vibration peak, which disappears after carbonization; this is because the CH bond is partially broken during the carbonization process, and the CF bond ratio increases. When PVP as a porogen is blended with PTFE / PVDF, the molecular chains are entangled and randomly distributed in the hollow fiber membrane; before carbonization, the peak is at 1675cm -1 The C=O characteristic peak of the residual PVP is at , which may be because the PVP was not completely dissolved during the phase transformation process; but the characteristic stretching vibration peak of CO disappeared after carbonization, indicating that the residual PVP in the carbonized membrane has been completely pyrolyzed. Compared with before carbonization, the spectrum of C-PTFE / PVDF shows a decrease in peak intensity, indicating that the content of some elements in C-PTFE / PVDF has decreased.

[0082] from Figure 3 It can be seen that the elements detected by XPS before and after carbonization of the PTFE / PVDF membrane embryo are mainly C, O, N, and F. Comparing the spectra of the PTFE / PVDF membrane before and after carbonization, it is found that the CO bond disappears in the carbonized C-PTFE / PVDF, which indicates that the CO double bond breaks during the carbonization process and PVP is completely pyrolyzed. The CF bond peak area in the membrane increases after carbonization, which is due to the breakage of the CH bond in PVDF during the carbonization process, resulting in an increase in the proportion of CF bonds in the membrane. Combining the FTIR and XPS spectra of the PTFE / PVDF membrane before and after carbonization, the CH bond in the membrane disappears, the proportion of CF bonds increases, and the surface energy of the CF bond is lower. Carbonization reduces the surface energy of C-PTFE / PVDF, verifying that carbonization may improve the hydrophobicity of the PTFE / PVDF membrane.

[0083] from Figure 4It can be seen that the cross-section of the PVDF / PTFE hollow fiber membrane embryo before carbonization in Example 1-Example 4 can be divided into three layers: finger-like holes on the inside and outside, and sponge-like holes in the middle. As the PTFE content in the membrane solution increases, the thickness of the finger-like holes on the inside and outside of the membrane also increases, and the sponge-like holes in the middle gradually decrease. This may be because during the phase transformation process, when the PTFE content is low, the PVDF content is high, and the phase transformation rate is slow, so thicker sponge-like holes are formed on the outside of the membrane; when the PTFE content is high, the PVDF content is low, so the phase transformation rate is fast, thereby forming larger finger-like holes, which is consistent with the research results of PVDF phase transformation into holes. Compared with the membrane embryo before carbonization, the membrane shrinks by 7.6% to 19.1%. Carbonization shrinks the sponge-like holes and finger-like holes in the membrane embryo, and the shrinkage of the finger-like holes is greater than that of the sponge-like holes. When the PTFE content is high, the large holes formed by the large-particle PTFE bridge shrink significantly and become ultra-micropores, and the membrane cross-section becomes more compact. This pore structure is conducive to the separation of particles of different particle sizes. This is because after the membrane embryo is carbonized, part of the CH bonds in PVDF are burned out to form a carbon-carbon structure, and the space between CH and CF collapses, which makes the pore size in the membrane embryo smaller. High-temperature carbonization also causes the PTFE particles to melt, causing the large pores formed by the PTFE bridge to shrink into small pores, filling the holes formed by the PVDF burned out by carbonization. The shrinkage and carbonization of the large pores cause the PTFE to melt and then fill the holes formed by the burned PVDF, which makes the carbonized membrane have a good separation efficiency.

[0084] from Figure 5 It can be seen that the water contact angle of the PTFE / PVDF hollow fiber membrane embryos before carbonization in Examples 1 to 4 increases from 84° to 92° as the PTFE content increases from 30% to 40%, indicating that the increase in PTFE content can improve the hydrophobicity of the membrane. However, when the PTFE content increases to 45%, the water contact angle of the membrane embryo decreases instead. This is because although the high porosity is conducive to the permeation flux of water, it also increases the risk of membrane wetting. Compared with the PTFE / PVDF membrane embryo, the contact angle of C-PTFE / PVDF increases to varying degrees, from 91° to 102°. When the PTFE content is 45%, the contact angle decreases instead, and the contact angle before and after carbonization does not change much.

[0085] from Figure 6It can be seen that the pore size of the PTFE / PVDF hollow fiber membrane before carbonization in Examples 1 to 4 gradually decreases with the increase of PTFE content; but when the PTFE content increases from 40% to 45%, the pore size of the membrane suddenly increases. Compared with the pore size of the membrane before carbonization, the pore size of the PTFE / PVDF hollow fiber membrane after carbonization is smaller. This may be because after the membrane is carbonized, PVDF is burned out to form space collapse; high temperature carbonization causes PTFE particles to melt and fill the holes formed by carbonization of PVDF, thereby causing the macropores formed by the PTFE particle bridge to shrink. The smaller pore size of the membrane after carbonization is consistent with the results of SEM observation.

[0086] from Figure 7 It can be seen that the PTFE / PVDF hollow fiber membranes in Examples 1-4 have a higher porosity before carbonization when the PTFE content is 30% and 35%, while when the PTFE content is increased to 40% and 45%, the porosity is relatively low. This is due to the increase in polymer concentration, which delays the solvent-non-solvent exchange and requires the polymer to undergo a longer phase transition. In addition, PTFE is an insoluble micropowder and may have a certain agglomeration (bridging) phenomenon, which is one of the reasons why the PTFE content in the PTFE / PVDF hollow fiber membrane before carbonization is high and the porosity is small. After carbonization, the porosity of the C-PTFE / PVDF hollow fiber membrane increases with the increase of the PTFE content. This is because as the PTFE content increases, the PTFE particles melt and connect during the carbonization process, filling the cavities formed by the carbonization of PVDF. But overall, the porosity of the PTFE / PVDF membrane before carbonization with the same PTFE content is greater than that of the C-PTFE / PVDF hollow fiber membrane after carbonization. This is because the PVDF is partially burned out during the carbonization process, and the PTFE particles melt at high temperature, causing the PTFE bridge to form the membrane pores, which are deformed and contracted by heat, resulting in a relatively lower porosity of the hollow fiber membrane after carbonization.

[0087] from Figure 8 (a) It can be seen that when the PTFE content of the PTFE / PVDF hollow fiber membrane before carbonization in Examples 1 to 4 increases from 30% to 40%, the elongation at break gradually decreases. This is because as the PVDF content decreases, the PTFE particles lose the connection support of the binder PVDF and cannot withstand the stretching required for the application, resulting in a decrease in the elongation at break of the membrane. Figure 8(b) It can be seen that: relative to the hollow fiber membrane before carbonization, the tensile strength of the hollow fiber membrane after carbonization of the PTFE / PVDF hollow fiber membrane in Examples 1 to 4 increased slightly, while the elongation at break decreased (1.5%-2.1%). The results show that the toughness of the hollow fiber membrane deteriorates after carbonization. This is because part of the PVDF in the membrane embryo is thermally decomposed after carbonization, and the support of the PVDF composed of carbon-carbon on the PTFE is reduced, resulting in a slight decrease in the elongation at break of the membrane, which is manifested in a decrease in the toughness of the membrane.

[0088] from Fig. 9 (a) and 9(b) show that in Examples 1 to 4, when the PTFE / PVDF content before and after carbonization is the same, the pure water flux of the fiber membrane after carbonization is higher than that before carbonization. This is because the surface roughness of the hydrophobic membrane material increases after carbonization, which increases the gas-liquid contact area on the membrane surface, thereby increasing the pure water flux of the membrane. Fig. 9 (a) and 9(b) show that when the PTFE content is 40%, the pure water flux of the carbonized hollow fiber membrane is the highest, and the total pure water flux reaches 467.67 L / (m 2 ·h·MPa).

[0089] from Fig.10 (b) It can be seen that in Examples 1 to 4, when the PTFE content in the membrane solution increases from 30% to 40%, the water flux of the membrane increases from 5 L / (m 2 ·h) increased to 30L / (m 2 ·h), indicating that the increase of PTFE content can improve the permeability of water in oil-water mixture. When the PTFE concentration is 40%, the separation efficiency of C-PTFE / PVDF membrane after carbonization can reach up to 80%. Continuing to increase the PTFE content, the water flux and separation efficiency of PTFE / PVDF and C-PTFE / PVDF membranes decrease instead. The decrease in separation performance due to the increase in PTFE content may be because the higher PTFE loading leads to excessive viscosity of the membrane liquid, which hinders the phase transformation between the solvent and the external gel medium in the membrane liquid, making it difficult to elute the PVP pore-forming agent in the membrane liquid, reducing the wettability of the membrane and resulting in reduced separation efficiency. The rough surface can provide growth nuclei for oil droplets, making it easier for them to contact each other, aggregate into large oil droplets, and begin to float under the influence of density difference to achieve oil-water separation. Therefore, the water flux and separation efficiency of C-PTFE / PVDF hollow fiber membrane after carbonization are higher than those before carbonization. The water flux and separation efficiency of C-PTFE / PVDF membrane after carbonization prepared with a PTFE content of 40% are the best, reaching 30L / (m 2 h) and 80%. This is the same as the previous Figure 6The pore size test results are consistent with that of the membrane. When PTFE is 40%, the minimum pore size of the membrane is 0.65μm, which can intercept more than 80% of the oil droplets larger than 0.65μm. The pore sizes of the membranes made with other compositions are all higher than 0.65μm, and the oil droplet size below 0.65μm in the oil-water mixture is less than 30L / (m 2 h), so the membrane with the smallest pore size has the best interception effect on the oil-water mixture. In Example 3, after the milky white oil-water mixture was filtered through the PTFE / PVDF hollow fiber membrane before and after carbonization, the permeate was clear and transparent, and the difference between the oil-water mixture before and after separation was obvious. Before separation, the oil-water mixture had a high oil content, was milky white, and had dense oil droplets and large particle size; the filtrate obtained by membrane filtration was clear and transparent, and very few small-particle oil droplets were shown in the optical microscope image, which shows that the hydrophobic PTFE / PVDF hollow fiber membrane prepared by the present invention can effectively achieve oil-water separation by separating the oil-water mixture, and the separation effect is remarkable.

[0090] from Fig.11 It can be seen that the separation efficiency of the C-PTFE / PVDF hollow fiber membrane in Example 3 shows a fluctuating downward trend. In each cycle, the oil-water separation efficiency is slightly lower than the previous one. This is because after each oil-water separation experiment, a part of the oil will adhere to the surface of the C-PTFE / PVDF membrane, and after cleaning, some separation performance can be restored. Although the oil-water separation efficiency of the membrane is reduced after multiple cycles, the separation efficiency is still above 74%, so the C-PTFE / PVDF hollow fiber membrane has good stability and cyclic performance.

[0091] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a C-PTFE / PVDF hollow fiber membrane for oil-water separation, characterized in that: include: Step 1: Place PTFE and PVDF powders in a drying oven for drying; Add PVDF and PVP into DMAc, stir until completely dissolved, then add PTFE powder, stir to obtain a membrane solution, and then transfer to a hollow fiber membrane spinning machine, let it stand and keep warm, and then use NIPS to prepare a PTFE / PVDF hollow fiber membrane embryo; Step 2: Take out the PTFE / PVDF hollow fiber membrane embryo from the deionized water and dry it naturally, then place it in a tubular furnace, use nitrogen as a protective gas, heat it to 380°C, keep it warm for 0.5h, cool it to room temperature and take it out to obtain a C-PTFE / PVDF hollow fiber membrane.

2. The method for preparing a C-PTFE / PVDF hollow fiber membrane for oil-water separation according to claim 1, characterized in that: In step 1, the PTFE and PVDF powders are placed in a drying oven and dried at 80° C. for 24 h.

3. The method for preparing a C-PTFE / PVDF hollow fiber membrane for oil-water separation according to claim 1, characterized in that: In step 1, PVDF and PVP were added to DMAc and stirred at 50°C until completely dissolved.

4. The method for preparing a C-PTFE / PVDF hollow fiber membrane for oil-water separation according to claim 1, characterized in that: In step 1, PTFE powder is added and stirred at 50° C. for 18 h to obtain a membrane solution.

5. The method for preparing a C-PTFE / PVDF hollow fiber membrane for oil-water separation according to claim 1, characterized in that: In step 1, after standing and keeping warm for 1 hour, a PTFE / PVDF hollow fiber membrane embryo is prepared using NIPS.

6. The method for preparing a C-PTFE / PVDF hollow fiber membrane for oil-water separation according to claim 1, characterized in that: The mass fraction of PTFE in the membrane liquid is 20% to 50%.

7. The method for preparing a C-PTFE / PVDF hollow fiber membrane for oil-water separation according to claim 6, characterized in that: In step 1, the mass fraction of PTFE in the membrane solution is 25% to 45%.

8. The method for preparing a C-PTFE / PVDF hollow fiber membrane for oil-water separation according to claim 1, characterized in that: In step 2, nitrogen was used as the protective gas, the temperature was raised to 380°C at 1°C / min, kept at that temperature for 0.5h, and then taken out after being cooled to room temperature.

9. A C-PTFE / PVDF hollow fiber membrane for oil-water separation, characterized in that: The membrane is prepared by the method for preparing a C-PTFE / PVDF hollow fiber membrane for oil-water separation according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Preparation method of hydrophilic polyvinylidene fluoride hollow fiber membrane

    CN109395593A

  • Modified PTFE (Polytetrafluoroethylene) hollow fiber membrane as well as preparation method and device

    CN113318615A

  • Modified spinning solution, hollow fiber carbon film, preparation methods of modified spinning solution and hollow fiber carbon film and application of hollow fiber carbon film

    CN113882038A

  • Polyamide porous membrane, filtration membrane module, and oil-water separation method

    JP2024134979A